Aspect of Justice in The Application of "Impoverishment" Concept in Asset Seizure Resulting from Corruption Offenses - Jaya, Arizon Mega; Maroni; Fardiansyah, A Irzal; Soerjatisnanta, Hieronymus; Akib, Muhammad; Jaya, Belardo Prasetya Mega (Jurnal Hukum dan Peradilan, 2025)
The main question and context of the discussion is whether the concept of impoverishment through asset confiscation in corruption cases in Indonesia fulfills the aspect of justice for defendants. This research will play a role in providing legal boundaries and certainty regarding the concept of impoverishment. This research used normative legal research. Normative legal research focuses on analyzing legal rules, principles, and doctrines to understand how the law should be, rather than how it is practiced. This research showed that the concept of impoverishing perpetrators of corruption crimes is interpreted as the confiscation of wealth/assets belonging to perpetrators of corruption crimes, which are the proceeds of corruption, and carried out in accordance with applicable regulations. Asset confiscation from perpetrators of corruption crimes must be implemented with legal measures that do not disregard the sense of justice and without disregarding or respecting the rights of the defendants and the property rights of others unrelated to the corruption case being handled, so the execution in the form of asset confiscation that can provide a sense of justice as it is conducted in a civilized manner and based on humanitarian values. Confiscating the wealth of defendants in corruption cases must be carried out proportionally, and the confiscation of individuals suspected of committing criminal acts of corruption must be upheld and must not violate constitutional principles.